Dapagliflozin Added to Usual Care in Individuals with Type 2 Diabetes Mellitus with Preexisting Cardiovascular Disease: A 24‐Week, Multicenter, Randomized, Double‐Blind, Placebo‐Controlled Study with a 28‐Week Extension. Issue 7 (2nd June 2014) - Leiter, Lawrence A.; Cefalu, William T.; de Bruin, Tjerk W. A.; Gause‐Nilsson, Ingrid; Sugg, Jennifer; Parikh, Shamik J.
<x xml:space="preserve">Abstract</x> Objectives To assess the efficacy of dapagliflozin, a sodium–glucose cotransporter 2 inhibitor, for the treatment of individuals with type 2 diabetes mellitus (T2DM) and preexisting cardiovascular disease (CVD). Design Randomized, double‐blind, age‐stratified (<65 and ≥65), 24‐week clinical trial with a 28‐week extension. Setting One hundred seventy‐three centers in 10 countries. Participants Individuals (N = 964) with T2DM, glycosylated hemoglobin (HbA1c) of 7.0% to 10.0%, and documented CVD. Intervention Dapagliflozin 10 mg/d or placebo was added to usual care. Participants receiving insulin had their total daily insulin dose reduced by 25% at randomization. Measurements Two equal primary end points: change from baseline in HbA1c and proportion of participants achieving a three‐item end point (reduction of ≥0.5% in HbA1c, ≥3% in body weight, and ≥3 mmHg in systolic blood pressure) at 24 weeks. Results Forty‐seven percent were aged 65 and older, 7.7% were aged 75 and older, mean duration of T2DM was 13 years, mean baseline HbA1c was 8.1%, and approximately 60% were taking insulin. The placebo‐corrected change in HbA1c with dapagliflozin was −0.4% at 24 weeks. Significantly more participants achieved the three‐item end point with dapagliflozin (10.0%) than with placebo (1.9%). The placebo‐corrected percentage change in body weight for dapagliflozin was −1.9% (−1.8 kg). Similar results were observed in both age strata, and changes were maintained over 52 weeks. More than one‐quarter (28.2%) of participants receiving dapagliflozin and 25.3% of those receiving placebo experienced hypoglycemia. More participants receiving dapagliflozin had vulvovaginitis, balanitis, or urinary tract infection. Conclusion When added to a usual background regimen in an older population with advanced T2DM and preexisting comorbid CVD, dapagliflozin improved glycemic control without an increase in hypoglycemic risk, promoted weight loss, and was well tolerated.